THE CURRENT OF UNBALANCE IN TURN-TO-TURN SHORT CIRCUIT IN THE WINDING OF TRANSFORMERS 6-10/0,4 кУ - S. K. Sheriazov; A. V. Pyatkov (Известия высших учебных заведений: Проблемы энергетики)
The procedure of defining the current of unbalance in turn-to-turn circuit in the winding of transformers is suggested in the article. The basic constituents of the current of unbalance are viewed. The results of experimental researches of currents of unbalance of direct and return sequence depending on the charge of transformer are given. On the results of theoretical and experimental researches the current of return sequence as the most sensitive parameter to the turn-to-turn circuit is defined.